Ovarian non-Hodgkin lymphoma with central nervous system involvement: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2023)
Background: Ovarian lymphoma is rare. Extranodal non-Hodgkin lymphoma (NHL) represents 0.5% of malignant genital diseases. Due to its rarity, there are no accepted treatment protocols. Diffuse large B cell lymphoma (DLBCL) has a central nervous system (CNS) involvement rate of 3-5%.Case presentation: A 38-year-old presented to the gynecological oncology clinic with abdominal pain and distension. Her tumor marker CA-125 levels were elevated. She developed right-sided facial nerve palsy and blindness. A diagnosis of aggressive NHL with a differential of DLBCL was made by histopathological and immunohistochemical examination of the excised ovarian tissue. A head computed tomography scan revealed subtle enhancing opacity suspicious of lymphomatous deposits. She was lost to follow-up after ten months of chemotherapy and cranial radiotherapy.Conclusion: Primary lymphoma of the ovary is rare, and the prognosis is often poorer when compounded with CNS involvement. Because of poor prognosis in the presence of CNS involvement, this case highlights the need for timely diagnosis and management.